Optimal management of primary focal segmental glomerulosclerosis in adults - Beaudreuil, Séverine (Int J Nephrol Renovasc Dis, 2017)
Focal segmental glomerulosclerosis (FSGS) is a frequent glomerular kidney disease that is revealed by proteinuria or even nephrotic syndrome. A diagnosis can be established from a kidney biopsy that shows focal and segmental glomerulosclerosis. This histopathological lesion may be caused by a primary podocyte injury (idiopathic FSGS) but is also associated with other pathologies (secondary FSGS). The first-line treatment for idiopathic FSGS with nephrotic syndrome is a prolonged course of corticosteroids. However, steroid resistance or steroid dependence is frequent, and despite intensified immunosuppressive treatment, FSGS can lead to end-stage renal failure. In addition, in some cases, FSGS can recur on a graft after kidney transplantation: an unidentified circulating factor may be implicated. Understanding of its physiopathology is unclear, and it remains an important challenge for the scientific community to identify a specific diagnostic biomarker and to develop specific therapeutics. This study reviews the treatment of primary FSGS and the recurrence of FSGS after kidney transplantation in adults.